Trade unionism in Public universities in Kenya: A Boon or a Curse to University leadership - Kithuri, Fr. Dr. Kinoti E.; Thuranira, Prof. Simon (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Trade unionism in Public universities in Kenya: A Boon or a Curse to University leadership AUTHORS Prof Thuranira, S. and Dr. Kinoti E. K. 1Meru University of Science and Technology Abstract A trade union is an organized association of workers formed for the protection and promotion of their common interests. The standard view of trade unions is that they are monopoly organizations that improve the welfare of members, principally by raising wages above the competitive level. This Study targets to investigate the conditions under which a union positively in a health way increases wages, and explores ways of modeling the competing preferences of unions and management. This descriptive, cross sectional study , explores trends in two measures of union power – union density and union coverage – over the period 2010 to the most recent year for which these data are available. In Kenya, there are several trade unions for different cadre of staff. Among them are Universities’ Academic Staff Union (UASU), Kenya Universities Staff Union (KUSU) and KUDHEHA. Universities’ Academic Staff Union (UASU) Universities’ Academic Staff Union (UASU) is a labor based union for academic staff in public universities in the Republic of Kenya which was registered in April 1966 as an organization called the University College Academic Staff Association was registered with the Registrar of Societies. The targeted population is all university staff member and a nonmember of the union, samples is present staff both in administrative academia and potential members working any university. The study utilize systemic review investigate conventional economic analysis help in defining and measuring the success of labor unions and democratic indicators unions. Utilizing secondary data analysis with emphasis on themes based on grounded theories in organizational structure, democracy, job satisfaction, negotiation theories are utilized as grounded theories to investigate in themes. These indicators combine two measures: union density and the relative union-nonunion wage gap. The indicators are applied to describe the movement of union welfare in the university settings over the past 15 years, the differences in union success among university staff workers, and the variation in union well-being across university. Population and sample; This study further investigated Union Membership and density, Challenges facing the trade union movement, function, role of unions in democratization of individuals, groups, and institutions. Results; Kenya has two federations, COTU (K) and TUC-Ke. There are about 50 registered trade unions, most of which (44) are affiliated to COTU (K) while a few such as the Kenya National Union of Teachers (KNUT), Union of Kenya Civil Servants (UKCS), Universities Academic Staff Union (UASU) and the Kenya Universities Staff Union (KUSU) affiliated to the newly formed Trade Union Congress of Kenya (TUC-Ke). Conclusion Kenya’s industrial relation is based on a fairly elaborate institutional and legal framework anchored on a tripartite set up. The set up brings together the government, workers (represented by trade unions) and employers (represented by employers’ organization). The legal framework is founded on relevant ILO Conventions ratified by the country, the country’s Constitution, and domestic labor. The study established that the trade unions mostly use letters, mails, notice boards as well as phone calls to communicate with their members and leaders. To make the unions visible, trade unions invested in the use of campaigns, proper representation and negotiation of pro worker CBAs that effectively address their concerns as workers. Most of the unions have engaged in social dialogue through CBA negotiations as well as in dispute resolutions to enhance industrial harmony. Through the social dialogue set up, most unions have been able to negotiate their CBAs.unions experience challenges which include Limited financial and human resources for the operations of the unions, Weak implementation of the labour laws as well as inefficient labour institutions. So many cases remained unresolved in the Employment and Labour Relations Court, Disunity, splits and rivalry among trade unions and trade union leaders breaking the solidarity spirit. There are also larger national climate that often has Anti- trade union Governance. The government has been slow in its dispute resolution processes as well as the enhancement of Alternative Dispute Resolution mechanisms. Many of the labour institutions lack capacity to perform their constitutional tasks as mandated, crippling industrial relations and Weak Trade union membership. Recommendations; Having a strong and well-structured leadership from the shop floor to the top management of the union Establishing an effective and fully functional organizing policy, strategy and team, Continuously sensitizing union leaders and members through education and training on labour laws and industrial relations, including sector specific labour matters, Pooling relevant human and capital resources for effective running of the union operations and most important internal democratization and accountability in union. KEYWORDS; UNION, union strategy, consensus, democracy, staff, Institutions